Egyptian and Indonesian Tafsir Literature: A Critical and Comparative Analysis - Faz, Ahmad Alim; Al Ayubi, Sholahuddin; Anwar, Endang Saeful (Riwayat: Educational Journal of History and Humanities, 2025)
Every work of interpretation will be inseparable from reality, certain tendencies, styles, characteristics and even different typologies. The background factor is the social-historical differences of each interpreter, including interpretive works in Egypt and Indonesia. The aim of this research is to understand the interpretive literature in Egypt and Indonesia using a crisis and comparative analysis approach. The research method used is that this research uses qualitative methods with a study focus on interpretive texts. A historical approach, especially the heuristic aspect, is used in order to trace historical traces, especially the connectivity of teaching the interpretation of the Koran between Egypt and Indonesia and the traces of influence of reform ideas. This research is library research. The results of research on the style and typology of interpretation in Indonesia are heavily colored by local Islam, both culture and conditions when the verses of the Quran are interpreted by the interpreter. Then, Indonesian interpretation also has a strong connection and attachment. with the Egyptian al-Azhar mindset which gave birth to many Indonesian scholars who indirectly contributed their thoughts in producing works of Indonesian interpretation.